Basic science for the MRCS a revision guide for surgical trainees - Raftery, Andrew T. (Churchill Livingstone/Elsevier, 2012)
A guide to the core basic sciences - anatomy, physiology and pathology - which comprise the essential knowledge required by the trainee entering the specialty of surgery. It focuses on those topics which tend to be recurring examination themes for initial surgical training.